PENGARUH LUAS LAHAN SAWAH DAN TENAGA KERJA PERTANIAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) SEKTOR PERTANIAN KABUPATEN LANGKAT - QUARTHANO REAVINDO, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The agricultural sector is the mainstay sector of Langkat Regency. This study aims to determine the effect of the area of ??paddy fields and labor in the agricultural sector on the Gross Regional Domestic Product (GRDP) of the agricultural sector in Langkat Regency. This study uses the method of Multiple Linear Regression Analysis. The results of this study indicate that the influence of rice field and agricultural labor force variables on the GRDP of the agricultural sector amounted to 67.1% while the remaining 32.9% was influenced by other factors not used in this study. The area of ??paddy fields and agricultural labor together have a significant effect on the GRDP of the agricultural sector but partially only paddy fields have an influence on the GRDP of the agricultural sector of Langkat Regency